Challenges and Prospects of Scheduled Caste People: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
No society is there, without the stratification, No society is there without the problem in the world. For example, Rome had plebeians problem, in Spartans “heltos’ problem, among the British “villains” problem, “ Egyptians ”slaves” problem, Americans ” Negroes” problem, Germans ”Jews” problem, like wise Hindus have the Harijans or the scheduled Caste people problem. The problems of slavery, serfdom …disappeared but the problem of Harijans or the scheduled Caste people still continued in India. These people are refered by different names like”untouchables”,”Harijans” “Backword’, “Depressed” “Panchamas” Chandalas” etc. in India. But Mahatma Gandhiji addressed them as “Harijans” the people of the God. The term ‘Scheduled castes’(Political-legal sense) was used for the first time by the simon commission (1928) under the Government of India Act of 1935, ‘Scheduled castes’ in independent Indian Consttution. More than 16 of Indian population is suffering from a number of disabilities like social problems (lowest status in the hierarchy- as a superior-inferior, civic disabilities (means they are not allowed to use public places facilities…), education facility, religious facility, no right of property ownership, political disabilities ….etc.